New trends of fundraising in Christian worship: the Nigerian pastoral experience - Anagwo, Emmanuel Chinedu (African theological studies, 2022)
"The last two decades have witnessed unprecedented trends of fundraising at the Eucharistic liturgy. Accordingly, this book, titled: New Trends of Fundraising in Christian Worship: The Nigerian Pastoral Experience, discusses the modern means of raising money and generating income at Christian worship by offering insightful liturgical analyses on the subject matter. It attempts to evaluate the true position of fundraising activities, as part of thanksgiving offerings, during celebrations, by drawing illuminations from the sacred scriptures, from the Church's tradition and her teachings, as well as from the Igbo-Nigerian Traditional Religion. Advocating the urgency to curb the excesses of prevalent abuses in the liturgy, this book is timely as it serves to educate, enlighten and re-orientate Catholics and others on the biblical and liturgical principles of fundraising for the Church's missionary enterprise"--